Introduksi Agro-Ekowisata pada Subak Sigaran - Sumiyati, S.; Tika, I W.; Budisanjaya, I.P.G. (Buletin Udayana Mengabdi; Vol 15 No 1 (2016): Jurnal Udayana Mengabdi)
Subak which has been recorded as part of the World Cultural Heritage (WCH) should be supported to maintain sustainability. One effort to support the sustainability of Subak Subak is to synergize with tourism. This is because Bali is still a major tourist destination in Indonesia. Subak Sigaran location close to tourist destinations Penatahan Hot Spring, so the development of agro-ecotourism is a potential alternative strategies for the empowerment of Subak Sigaran. But for the empowerment, there are some constraints such as the condition of supporting infrastructure of agro-ecotourism is still not adequate, and the areas that have the potential to be trekking developed is dirty. The activities implementation as step solution is to do the cleaning of irrigation channels and some parts of the trekking paths are planned, and built a toilet as part of efforts to complete the supporting infrastructure. To enhance awareness of Subak members associated with cleanliness, conducted socialization activities.
Keywords: Subak, agro-ecotourism, empowerment, World Cultural Heritage (WCH).